INTEGRATION OF ACCOUNTING SYSTEMS IN BUSINESS MERGERS - Rezy Trilestari; M. Ibnu Suganda; Suhaimi; Yoana Badra; Ulfah; Indrayani; Muammar Khaddafi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
The conclusions that can be drawn based on the discussion and explanation above are as follows: Acquisition is an effective strategy that can be used by companies to increase corporate value and competitive advantage. To achieve this, companies must consider various decisions and plan carefully to reach strategic decisions. The challenges faced by the company immediately after the acquisition were challenges to integrity, cultural factors, systems and procedures that differed between companies, which required adjustments. If the company cannot handle this challenge properly, it will cause acquisition failure. The impact of implementing the acquisition has not shown consistent results and on average it shows a decrease in the company's financial performance after the acquisition so that further studies are needed and the company should evaluate the effectiveness of the acquisitions carried out and be able to optimize available resources.